Interferon alpha induces sustained changes in NK cell responsiveness to Hepatitis B viral load suppression in vivo. - Gill, US; Peppa, D; Micco, L; Singh, HD; Carey, I; Foster, GR; Maini, MK; Kennedy, PTF (Public Library of Science, 2016)
NK cells are important antiviral effectors, highly enriched in the liver, with the potential to regulate immunopathogenesis in persistent viral infections. Here we examined whether changes in the NK pool are induced when patients with eAg-positive CHB are 'primed' with PegIFNα and importantly, whether these changes are sustained or further modulated long-term after switching to nucleos(t)ides (sequential NUC therapy), an approach currently tested in the clinic. Longitudinal sampling of a prospectively recruited cohort of patients with eAg+CHB showed that the cumulative expansion of CD56bright NK cells driven by 48-weeks of PegIFNα was maintained at higher than baseline levels throughout the subsequent 9 months of sequential NUCs. Unexpectedly, PegIFNα-expanded NK cells showed further augmentation in their expression of the activating NK cell receptors NKp30 and NKp46 during sequential NUCs. The expansion in proliferating, functional NK cells was more pronounced following sequential NUCs than in comparison cohorts of patients treated with de novo NUCs or PegIFNα only. Reduction in circulating HBsAg concentrations, a key goal in the path towards functional cure of CHB, was only achieved in those patients with enhancement of NK cell IFNγ and cytotoxicity but decrease in their expression of the death ligand TRAIL. In summary, we conclude that PegIFNα priming can expand a population of functional NK cells with an altered responsiveness to subsequent antiviral suppression by NUCs. Patients on sequential NUCs with a distinct NK cell profile show a decline in HBsAg, providing mechanistic insights for the further optimisation of treatment strategies to achieve sustained responses in CHB.